A propensity score analysis on the effect of on-pump versus off-pump coronary artery bypass grafting for patients with coronary artery disease - Liu, Peng; Wang, Fei; Ren, Shiyan; Lin, Fan; Yang, Yuguang; Fan, Xueqiang; Sun, Guang; Zheng, Xia; Liu, Jiangtao; Yuan, Jing; Ye, Zhidong (Journal of Thoracic Disease, 2014)
Aim: The aim of this retrospective observational study was to investigate the effect of on-pump versus offpump coronary artery bypass grafting (CABG) for patients with coronary artery diseases (CAD). Methods: A retrospective observational study was performed using a propensity score analysis in 290 consecutive patients undergoing CABG between April 2009 and March 2014, of them, 54 patients undergoing off-pump CABG (OPCABG) were matched with 54 patients undergoing on-pump CABG (ONCABG) by propensity score. The perioperative complications and hospital mortality were documented. Results: Preoperative characteristics were comparable in both groups following propensity matching. Postoperative myocardial infarction (MI) incidence was lower in OPCABG group than in ONCABG group (3.7% vs. 14.8%, P=0.046); both hospital mortality and the major complications rates were similar in the two groups after propensity adjustment for preoperative characteristics. Conclusions: The perioperative complications are similar in both off-pump and on pump CABG groups, the short-term effect of OPCABG is similar to that of ONCABG.